Making the Nile River a Point of Cooperation between Ethiopia and Egypt: Building Confidence through Water Diplomacy - Enku Tensay Woldemaryam (Budapest International Research and Critics University, 2020)
Transboundary water resources interconnect different nations that can have a viable interest on the water resources. That variety of interests on the same water resource sometimes creates differences among the parties. Acknowledgement of the differing interests of relevant actors has paramount importance to settle water disagreement. The current Nile disagreement issue between Ethiopia and Egypt is out of the academic scope and only become partial news coverage point of the News Media on both side. Partial reporting of the problem will only increase tension among the nations and brings insecurity. Thus this study will bring impartial analysis of the problem by considering the interest of both sides to settle the problem through water diplomacy. The study will try to provide the importance of water diplomacy in solving the Nile River conflict between Ethiopia and Egypt. In conducting this study, the researcher will analyze all relevant literatures related with water disagreement and water diplomacy to shade light on the problem and propose a solution.